Uma ilha sem mulheres : as relações de gênero nos suplementos literários da imprensa recifense em fins da década de 1920 - AMARAL, Tércio de Lima (2015)
This research analyzes the representations of gender relations pursuant to press during entertainment journalism development in the city of Recife in the end of First Republic (1889-1930). In this regard, they are used as sources the Newspapers Diario de Pernambuco, between June 1924 and June 1925, and Diario da Manhã, between April 1927 and April 1928. Both Newspapers were pioneers in the publication of special sections and pages turned to literature and, they kept, in the recifense press, supplements with duration bigger than a year in the 1920 decade. This study aims to show up how the social, cultural and economic changes frame was insert in the supplements at the moment in which lettered elite defended new modernity practices in the urban centers. Discussions around themes as the feminine vote, divorce and feminism were in these special pages. These supplements identified these new demands, and, in several moments, positioned themselves against them, especially when the subject involved the relation between men and women. Space to tale, poetries, articles and illustrations dissemination, the supplements revealed national important names of literature and arts who had in journalism their first professional experience, as Gilberto Freyre, Lula Cardoso Ayres and Josué de Castro, among other people. This is a distinct and pioneer experience in Brazilian and Pernambucano journalism history, achieving its height and ending in the 1940 and 1950 decades.